2011
DOI: 10.1177/1471301211421264
|View full text |Cite
|
Sign up to set email alerts
|

‘The problem with Leonard’: A critical constructionist view of need-driven dementia-compromised behaviours

Abstract: This critical constructionist case study of 'Leonard,' a man with frontotemporal dementia living on a special care unit predominantly populated by people with Alzheimer's disease and related dementias, explores how healthy others' perceptions of the prevailing physical and psychosocial environment were influenced by Leonard's behaviour which, in turn, was influenced by people's perceptions of him as a 'problem'. Data were obtained through participant observations, individual interviews with staff and residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Resident-to-resident psychological abuse and material exploitation has been studied less extensively, with only four studies exploring this type of resident-toresident abuse. However, nursing home staffs have reported that threats and intimidation techniques are recurrent forms of resident-to-resident abuse (Castle, Lapuk ( 2007 ) Yelling, screaming, cursing Pillemer et al ( 2012 ) Insults, mean-spirited comments, sarcasm Screaming/yelling, telling others to "shut up", cursing, arguing, bossing around, racial slurs Physical Castle ( 2012 ) Pushing, grabbing, pinching, kicking Lachs et al ( 2007 ) Aggravated assault, simple assault Lapuk ( 2007 ) Punching, whipping, pounding, fi ghting Malone et al ( 1993 ) Hitting, grabbing, throwing, kicking, pinching, pushing, scratching, biting Pushing, punching, fi ghting over food, slapping, ramming with wheelchair Psychological Castle ( 2012 ) Threats, intimidation, critical remarks Pillemer et al ( 2012 ) Jeering, teasing, threats Threats, intimidation Sexual Abuse Castle ( 2012 ) Fondling, exposure of private body parts, unwelcome sexualized kissing, discussions of sexualized activities Pillemer et al ( 2012 ) Intentional nudity, unwanted sexual advances Ramsey-Klawsnik et al ( 2008 ) Inappropriate interest in body, fondling/molestation, sexualized kissing Attempting to get into bed, inappropriate touching, verbal sexual abuse Teaster & Roberto ( 2003 ) Sexualized kissing, fondling, unwelcome sexualized interest in body, sexual jokes/comments, unwelcome sexualized discussion Teaster & Roberto ( 2004 ) Unwelcome sexualized interest, unwelcome sexualized discussions, sexual jokes/comments, sexualized kissing, fondling Teaster et al ( 2007 ) Fondling, inappropriate interest in body Material Exploitation Castle ( 2012 ) Theft of possessions, theft of assets Koehn et al ( 2011 ) Theft of food, theft of possessions Pillemer et al ( 2012 ) Theft of possessions Theft of possessions 2012 ; Pillemer et al, 2012 ;. Furthermore, theft of possessions (Castle, 2012 ;Pillemer et al, 2012 ; and theft of food (Koehn, Kozak, & Drance, 2011 ) were common forms of material exploitation.…”
Section: Type Of Resident-to-resident Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Resident-to-resident psychological abuse and material exploitation has been studied less extensively, with only four studies exploring this type of resident-toresident abuse. However, nursing home staffs have reported that threats and intimidation techniques are recurrent forms of resident-to-resident abuse (Castle, Lapuk ( 2007 ) Yelling, screaming, cursing Pillemer et al ( 2012 ) Insults, mean-spirited comments, sarcasm Screaming/yelling, telling others to "shut up", cursing, arguing, bossing around, racial slurs Physical Castle ( 2012 ) Pushing, grabbing, pinching, kicking Lachs et al ( 2007 ) Aggravated assault, simple assault Lapuk ( 2007 ) Punching, whipping, pounding, fi ghting Malone et al ( 1993 ) Hitting, grabbing, throwing, kicking, pinching, pushing, scratching, biting Pushing, punching, fi ghting over food, slapping, ramming with wheelchair Psychological Castle ( 2012 ) Threats, intimidation, critical remarks Pillemer et al ( 2012 ) Jeering, teasing, threats Threats, intimidation Sexual Abuse Castle ( 2012 ) Fondling, exposure of private body parts, unwelcome sexualized kissing, discussions of sexualized activities Pillemer et al ( 2012 ) Intentional nudity, unwanted sexual advances Ramsey-Klawsnik et al ( 2008 ) Inappropriate interest in body, fondling/molestation, sexualized kissing Attempting to get into bed, inappropriate touching, verbal sexual abuse Teaster & Roberto ( 2003 ) Sexualized kissing, fondling, unwelcome sexualized interest in body, sexual jokes/comments, unwelcome sexualized discussion Teaster & Roberto ( 2004 ) Unwelcome sexualized interest, unwelcome sexualized discussions, sexual jokes/comments, sexualized kissing, fondling Teaster et al ( 2007 ) Fondling, inappropriate interest in body Material Exploitation Castle ( 2012 ) Theft of possessions, theft of assets Koehn et al ( 2011 ) Theft of food, theft of possessions Pillemer et al ( 2012 ) Theft of possessions Theft of possessions 2012 ; Pillemer et al, 2012 ;. Furthermore, theft of possessions (Castle, 2012 ;Pillemer et al, 2012 ; and theft of food (Koehn, Kozak, & Drance, 2011 ) were common forms of material exploitation.…”
Section: Type Of Resident-to-resident Abusementioning
confidence: 99%
“…A prominent recommendation in the literature highlighted the need for staff and family to receive education and training on resident-to-resident abuse to enhance protection of residents in nursing facilities (Koehn et al, 2011 ;Robinson & Tappen, 2008 ;Teaster & Roberto, 2003 ;Teresi et al, 2013 ;Williams, 2004 ;Zhang et al, 2012 ). Teresi et al ( 2013 ) evaluated a resident-toresident elder mistreatment staff intervention-training program.…”
Section: Interventions For Resident-to-resident Abusementioning
confidence: 99%
“…However, there are reasons to believe that those unmet needs differ according to the type of dementia (Koehn et al . ). Therefore, it is necessary to determine whether this assumption is transferable to people with bvFTD.…”
Section: Discussionmentioning
confidence: 97%
“…[25]. Some of these may concern ritualistic behavior and talk [26]. However, research concerning person-centered care for PWDs argues that social interaction is a basic human need and that active participation from all participants is a part of successful collaborative communication with PWDs [2].…”
Section: Discussionmentioning
confidence: 99%